Cystatin C level and amikacin use in neonatal sepsis - Putu Diah Pratiwi; I Wayan Dharma Artana; Ni Putu Veny Kartika Yantie; Hendra Santoso; I Gusti Ngurah Sanjaya Putra; Gusti Ayu Putu Nilawati; Ni Nyoman Metriani Nesa (Indonesian Pediatric Society, 2020)
Background Amikacin is the antibiotic of choice for eradicating bacteria in neonatal sepsis because of its effectiveness against Gram-negative bacteria. However, this drug has nephrotoxic effects. Monitoring kidney function in neonates is very important because amikacin can interfere with development of the kidney. Several studies have shown that serum cystatin C levels were closer to glomerular filtration rate (GFR) values ​​compared to serum creatinine levels. Objective To evaluate cystatin C levels before and after administration of amikacin in neonates with sepsis. Methods This prospective cohort study was conducted in one group with a pretest and posttest design. Thirty neonatal sepsis patients who received amikacin therapy at Sanglah General Hospital, Denpasar, Bali, were included by consecutive sampling. Their cystatin C levels were measured before and after receiving amikacin therapy. Data were normally distributed and analyzed by paired T-test, with a value of P<0.05 considered to be significant. Results The mean difference was 0.23 [1.57 (SD 0.29) vs. 1.80 (SD 0.28)] mg/L with P value < 0.001. There was different value of cystatin c level before and after amikacin therapy with deviation standard 0.25 with P<0.001 (alfa 5%). Conclusion Cystatin C levels are significantly higher in neonates with sepsis after administration of amikacin.